Digital Transformation of BPRACo by Designing IT Governance with COBIT 2019 SME Focus Area - M. Agung Rizaldi; Rahmat Mulyana; Luthfi Ramadani (Universitas Sains dan Teknologi Komputer, 2024)
Digital transformation (DT) is a necessity for incumbent companies today, including MSMEs, to be able to continue to compete in the era of technological disruption and accelerated by the COVID-19 pandemic. This research aims to design IT governance (ITG) for BPRACo MSMEs using the COBIT 2019 SME focus area framework. The research method used is design science research (DSR) which creates artifacts in the form of ITG solution development methods and systems. The research results revealed that the highest GMO priorities selected were APO10 Managed Vendors, MEA03 Managed Compliance with External Requirements, and APO12 Managed Risk. From the analysis of the selected GMOs, there are gaps and recommendations for improvement in the seven components which are then mapped into three aspects, namely people, process and technology aspects. The results of the research analysis show that the ambidextrous IT governance approach has succeeded in increasing the level of capability in several main components of BPRACo MSMEs in adopting DT. The right ITG strategy can help BPRACo MSMEs operating in the banking industry achieve a successful DT journey.